Design and simulation of microstrip patch array antenna with HFSS for 2.45GHz applications - Trương Ngọc Hà, (Journal of Technical Education Science, 2021)
This paper studied the application of microstrip antenna array for operation at 2.45GHz frequency. In this paper, the theoretical bases as well as the formulas about microsequence antennas are applied by the author to calculate and design a microstrip antenna. Then, the author designed two element antennas and four element antenna arrays with parallel power method. The HFSS v13 software is used to evaluate the antenna parameters: resonant frequency, radiation pattern, efficiency, gain. As final, the study showed that with 1x4 microstrip antenna array, the results are as follows: gain=9.7(dB), radiation efficiency=95.7%, resonant frequency=2.45GHz with bandwidth(BW)=90MHz and the maximum radiation direction of the array antenna θ=00.